Prevalence Rate and Etiology of Drug Abuse among Preparatory and High School Students in Addis Ababa, Ethiopia - Michael, Messeret Assefa Wolde (JOURNAL OF INDIAN EDUCATION, 2010)
The study examines the etiology and prevalence of drug abuse among preparatory and high school students in Addis Ababa. The method employed was mixed method, i.e., quantitative and qualitative. The research was conducted on a target population of 814 students from 8 preparatory and high schools with prior exposure to such drugs as Khat, tobacco and alcohol. The subjects were chosen based on simple random sampling from grades 9–12 and were requested to give information as to their experience towards the mentioned drugs consensually. Among other things, the findings suggested that female students to be the biggest abusers of alcoholic drinks while the male ones outnumber female students in the use of multiple drugs. Furthermore, it was found out that such factors as curiosity and company of friends attracting high school students toward drug abuse. Based on a thorough assessment of the findings in the present research, the investigator is of the opinion that: Better management within preparatory and high schools, familiarising students with the dangers of drug abuse and restriction on the latter’s access to drug vending business and/or drug-friendly atmosphere to be instrumental in curbing drug abuse among preparatory and high school students and the prevalence thereof.